Opieka pielęgniarska nad pacjentem w kryzysie bezdomności - Maciaszek-Tume, Adrianna (Kultura-Społeczeństwo-Edukacja, 2025)
The nursing care of patients experiencing homelessness presents a unique challenge, requiring a holistic, empathetic, and interdisciplinary approach. Homelessness is a complex social problem that significantly impacts both physical and mental health. Nurses, often the first point of contact for homeless individuals, play a critical role in providing comprehensive care that extends beyond traditional medical interventions. This literature review aims to analyze the specificity of nursing care for patients in a homelessness crisis, highlighting the application of theoretical nursing models to support holistic care. The study identifies major health challenges among homeless populations, including infectious and chronic diseases, mental health disorders, and injuries, and emphasizes the importance of understanding patients’ living conditions, such as instability, malnutrition, and poor hygiene. Key aspects of effective nursing care include building trust-based relationships, demonstrating empathy, and advocating for systemic changes through collaboration with social services and non-governmental organizations. The findings support practical recommendations for healthcare systems, including staff training, development of mobile and specialized care programs, integration of healthcare and social services, and active participation of nurses in shaping public health policies. This review underscores the vital role of nurses in improving health outcomes and quality of life for individuals experiencing homelessness.